Analysis of Dental Specialty Center target achievement and associated factors, Brazil, 2019-2022: a cross-sectional study - Luciana Leônia Soares Freire; Rênnis Oliveira da Silva; Rilary Rodrigues Feitosa; Lucas Xavier Bezerra de Menezes; Renato Taqueo Placeres Ishigame; Yuri Wanderley Cavalcanti; Edson Hilan Gomes de Lucena (Epidemiologia e Serviços de Saúde, 2025)
Abstract Objective To evaluate the performance of Dental Specialty Centers in Brazil from 2019 to 2022 and analyze its association with contextual factors. Methods This is an observational, cross-sectional, descriptive, and analytical study. We used secondary data on Dental Specialty Center production collected from the Outpatient Information Systems. We used a robust Poisson multiple regression model to determine the target achievement prevalence ratio (PR). We calculated 95% confidence intervals (95%CI) for the variables under study. Results Poor performance, with achievement of 0-3 targets, prevailed in the Dental Specialty Centers. Among the dental procedures, targets related to general basic procedures had the best result, with the highest achievement of targets. Dental Specialty Centers located in regions with more than 100,000 inhabitants had a higher frequency of target achievement (PR 1.68; 95%CI 1.26; 2.29). In 2020 (PR 0.10; 95%CI 0.07; 0.15), 2021 (PR 0.22; 95%CI 0.16; 0.28) and 2022 (PR 0.48; 95%CI 0.39; 0.59) target achievement prevalence was lower than in 2019. Conclusion Most Dental Specialty Centers performed poorly in achieving their targets. Municipalities with larger population sizes were more likely to achieve their targets. The COVID-19 pandemic negatively influenced their performance.